SCIAMACHY's View of the Polar Atmosphere - Gottwald, Manfred; Krieg, Eckhart; von Savigny, Christian; Noel, Stefan; Reichl, Philipp; Richter, Andreas; Bovensmann, Heinrich; Burrows, John P. (SCIAMACHYÃ¢â¬â¢s View of the Polar Atmosphere, 2007)
SCIAMACHY observed the polar atmosphere in the past 5 years in great detail. We present several examples of geophysical parameters retrieved from these measurements. Starting in the troposphere we discuss interactions between the arctic ocean and tropospheric trace gases. One layer up in the stratosphere catalytic ozone depletion is still a major concern with several participating key species being monitored continuously. During the ozone hole episodes PSCs are detected and yield insight into the underlying chemical processes. Finally the mesosphere hosts NLCs which are considered to be an early indicator of global change. SCIAMACHY’s measurements allow not only identification of NLCs but also of their particle sizes. The polar atmosphere is considered to be highly sensitive to anthropogenic impacts on the Earth system and thus to climate change. SCIAMACHY’s measurements contribute significantly to the understanding of the underlying atmospheric chemistry and transport processes